MENGGAGAS MUNĀSABAH ALQURAN: PERAN DAN MODEL PENAFSIRAN ALQURAN - Hasani Ahmad Said (Hunafa: Jurnal Studia Islamika, 2016)
The Quran has the miracle of each of its dimensions, it can be understood as presented al-Zarkasyī that the Quran was not revealed by accident, by chance, and without specific goals and objectives. Accordingly, any use and wording (lafadz), construction of verses and letters (munāsabah baina al-āyāt wa al-sūrah) and transitional themes contained in, it has the power concept as a kalam intact and coherent (muttasiqāt al-mabānī wa muntadzimāt al-ma’ānī ka al-kalimah al-wāhidah). And the whole Quran is meet that requirement, which consists of 30 chapters, 114 letters, nearly 88,000 words and more than 300,000 letters, as asserted Al-Qurtubi (641) is like a letter that cannot be separated. Thus, the unity of the Quran is happening at all is not as forced, but it can be proved through the relationship between section by section. The birth of the knowledge of the conformity (Munāsabah), originate from the fact that the Quran systematic as contained in Ottoman manuscripts now is not based on chronological descent. That is why there is a difference of opinion among scholars Salaf on the order of letters in the Quran. This paper will address concerns about the chronological arrangement of the Quran